Influence of Current Collector and Cathode Area Discrepancy on Performance Evaluation of Solid Oxide Fuel Cell with Thin-Film-Processed Cathode - Son, Ji-Won; Song, Hue-Sup (KOREAN SOC PRECISION ENG, 2014)
The influence of the area difference between the current collector and the thin-film-processed cathode on the performance evaluation of the solid oxide fuel cell (SOFC) is investigated Two 2 cm by 2 cm anode supported SOFCs with a I cm by I cm cathode (Cell-1.0) and a 1.5 cm by 1.5 cm cathode (Cell-2.25) are fabricated and the performances are measured in a button cell test set-up with a cathode current collection area of 1 cm by 1 cm. Significantly different cell power outputs are measured. The total power output of the Cell-2.25 is 1.35 similar to 1.68 times to that of the Cell-1.0. The discrepancy is considered to originate from two major reasons: 1. limited lateral conduction and 2. thin thickness of the cathode. The cell performance can be overestimated when the smaller area is chosen, or underestimated when the larger area is chosen as the active area between the current collection area and the cathode area. The present study identifies another important factor to be considered to exactly assess the performance of the SOFC implementing thin-film-processed electrode.
Keywords: PULSED-LASER DEPOSITION; TEMPERATURE; MICROSCOPY; SOFC